Who cares for orphans? Challenges to kinship and morality in a Luo village in Western Kenya - Cooper, EC (2011)
This dissertation analyses an ethnographic study of how people in a peri-urban, agricultural village in western Kenya have responded to the questions of who will care for children, and how, when those children’s parents, or other primary caregivers, have died. It examines the practical and ideological implications of wide-scale orphaning among a population that has experienced increased numbers and proportions of orphaned children mainly due to HIV/AIDS, as well as the gradual depletion of resources in terms of both the availability of middle-aged adults and the security of economic livelihoods. The research explores how specific caring relationships, as well as general sociality, have been challenged, adapted, and affirmed or rejected normatively and practically in this context. The research revealed a high degree of questioning in people’s efforts to forge responses to children’s orphaned situations. Rarely was there unambiguous consensus in the study context concerning what should be done in response to children’s orphanhood in light of families’ diminished livelihood capacities. More broadly, there was a distinctive concern with how such situations might be appraised in moral terms. The analysis therefore focuses on three main concerns, including: how to understand uncertainty as a condition of life, and the implications of this; how a shared perspective of uncertainty has spurred a concern with morality in the study context, and specifically galvanised a moral economy of kinship; and how the concern with morality affected what was deemed at stake in people’s lives.